Commonly Observed Sex Differences in Direct Aggression Are Absent or Reversed in Sibling Contexts - Fernandez-Tapia, A; Barbato-Epple, M (OXFORD UNIV PRESS, 2025)
Decades of research support the generalization that human males tend to be more aggressive than females. However, most of that research has examined aggression between unrelated individuals. Data drawn from 24 societies around the globe (n = 4,013) indicate that this generalization does not hold in the context of sibling relationships. In retrospective self-reports, females report being at least as aggressive as males toward their siblings, often more so. This holds for direct as well as indirect aggression, and for aggression between adult siblings as well as aggression that occurred during childhood. Consistent with prior research on sex differences, males reported engaging in more direct aggression toward nonkin than did females in the majority of societies. The results suggest that the dynamics of aggression within the family are different from those outside of it, and ultimately that understanding the role of sex in aggressive tendencies depends on context and target.